Bear with me: Understanding motivations for bear farming in Vietnam - Green, Jennah; Schmidt-Burbach, Jan; Kukreja, Karanvir; Guillon, Elodie (Frontiers in Conservation Science, 2022)
Bears were once farmed legally across Vietnam to supply bile, a digestive fluid, as an ingredient for traditional medicine products. Extracting and selling bear bile has been prohibited in Vietnam since 2005, but there is evidence that an illegal industry remains active. The aim of this study is to gain insight into the motivations and experiences of Vietnamese bear farmers. Thirty-seven semi-structured interviews were conducted with 28 active and 9 former bear farmers across 14 provinces in Vietnam. Our findings confirm previous reports in the literature that there is still an active, illegal bear bile market in Vietnam, but that bear farming is becoming less profitable due to a reduction in demand for farmed products and the decreasing price of bile. Additional results indicate that many Vietnamese bear farmers may have a poor understanding of regulations governing the trade of bear parts and that most farmers do not intend to stop farming bears. Based on these findings, we suggest the most effective method of persuading bear farmers to stop trading bile would be via former bear farmers and to reduce the social acceptability of bile consumption throughout the country. We hope the results of this study can help refine strategies and inform future efforts to end the bear bile industry in Vietnam.